Challenges experienced by post coronary artery bypass grafting patients: A qualitative study from Peshawar, Khyber Pakhtunkhwa, Pakistan - Israr Ahmad; Sardar Ali; Nasreen Ghani; Asmat Shaheen (Journal of the Pakistan Medical Association, 2021)
Objective: To explore the experiences of post-coronary artery bypass grafting patients in Pakistan. Method: The qualitative, descriptive, phenomenological study was conducted at the Lady Reading Hospital, Peshawar, Pakistan, from May 2018 to April 2019, and comprised patients having undergone coronary artery bypass grafting. Data was collected through semi-structured interviews that included probing questions. Codes, categories and themes were framed through extensive thematic analysis. Results: Of the 14 patients, 11(78.6%) were males with a mean age of 51 years, and 3(21.4%) were females with a mean age of 63 years. Four main themes were generated; challenges, perceptions about coronary artery bypass grafting, coping with the challenges, and perceptions about nurses and doctors. The subjects were of the view that they were affected with certain types of physical, psychological and financial challenges. These encounters affected the patients post-procedure in almost every aspect of their lives and made it difficult for them to carry out activities on a daily basis. Further, coping strategies varied on from individual to individual. Conclusion: Patients after coronary artery bypass grafting were found to encounter issues related to physical, psychological and social spheres. Care for such patients must be planned in a way to avoid such challenges. Continuous...